2019
DOI: 10.3390/su11246993
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of Entrepreneurial Intention among Young People: Model and Regional Evidence

Abstract: Entrepreneurial intentions determine to a large extent the entrepreneurial behavior; therefore, the study of those intentions and the factors that influence them constitute a valid research area. The purpose of this regional comparative study was to design a new causal model of the formation of the entrepreneurial intention among young adults in Spain and Poland. Using the Structural Equation Modeling (PLS) methodology, the results show that subjective variables (beliefs, social norms, values) initiate the cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(68 citation statements)
references
References 181 publications
7
54
0
Order By: Relevance
“…Similar to the intrinsic and extrinsic motivation approach, the proposed model includes internal and external consumer variables. In the literature on consumer behavior, there are some similar models [84]. However, it should be noted that the relationship between reputation, trust, and satisfaction, or between social norm, attitude, and intention, which are included in this study, are novel in the literature [85].…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Similar to the intrinsic and extrinsic motivation approach, the proposed model includes internal and external consumer variables. In the literature on consumer behavior, there are some similar models [84]. However, it should be noted that the relationship between reputation, trust, and satisfaction, or between social norm, attitude, and intention, which are included in this study, are novel in the literature [85].…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…This nurtures their willingness to start a business ( Panagiotis and Dimo, 2015 ). Martínez-González et al (2019) found that subjective factors (beliefs, social norms, and values) initiate a chain of events, which influence action variables (motivation, self-efficacy, and intention). Emotional competence is also a subjective variable.…”
Section: Research Hypothesesmentioning
confidence: 99%
“…It is essential to understand what factors drive entrepreneurial behaviour [63]. Some aspects of this behaviour depend on objective sociodemographic variables (e.g., age, gender, educational level or employment status), while others depend on an individual's subjective characteristics (e.g., their perceptions and preferences) [64,65].…”
Section: Theoretical Framework and Development Of Hypothesesmentioning
confidence: 99%